Analisis Kebisingan Daerah Perkotaan (Studi Kasus Kawasan PLTD Kabupaten Fakfak) - Jusmawandi Jusmawandi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Noise generated by Diesel Power Plants (PLTD) is a significant environmental problem, especially in urban areas and settlements adjacent to power plant facilities. This study analyzes the noise level around the Fakfak Cotton Plant and its impact on the local community. This study uses a combination of methods, including noise level measurements using a Sound Level Meter (SLM), field observations, interviews with the community, and a SWOT analysis to evaluate the strengths, weaknesses, opportunities, and threats in noise mitigation. The measurement results show that the noise level generated exceeds the threshold of 55 dBA set by the Decree of the Minister of Environment Number 48 of 1996 for residential areas. This condition has a negative impact on the comfort, health, and social interaction of the community around the PLTD location, causing sleep disturbances, stress, and decreased quality of life. The SWOT analysis shows that although the PLTD has advantages in terms of sustainable operations and professional workers, the main weaknesses lie in the lack of soundproofing and the absence of regular noise evaluations. However, there is a great opportunity in the application of noise mitigation technologies, such as the installation of soundproofing, the use of acoustic walls, and planting vegetation as a sound barrier. In addition, collaboration with local governments and increasing environmental awareness can help manage noise impacts more effectively. The main threats identified include potential social conflicts with surrounding communities, negative health impacts, and changes in environmental policies that can affect PLTD operations. With the right mitigation strategies, such as the application of soundproofing technologies, improved communication with the community, and better integration of environmental policies, the environment around PLTDs can become more comfortable and conducive for the community. This study emphasizes the importance of regulatory and technology-based approaches in managing noise in urban environments, as well as the need for sustainable mitigation measures to maintain the well-being of communities around PLTDs..